2011
DOI: 10.1186/1756-9966-30-66
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine induces human pancreatic cancer PANC-1 cells apoptosis via regulating expression of Bcl-2 and IAP families, and releasing of cytochrome c

Abstract: BackgroundOxymatrine, an isolated extract from traditional Chinese herb Sophora Flavescens Ait, has been traditionally used for therapy of anti-hepatitis B virus, anti-inflammation and anti-anaphylaxis. The present study was to investigate the anti-cancer effect of oxymatrine on human pancreatic cancer PANC-1 cells, and its possible molecular mechanism.MethodsThe effect of oxymatrine on the viability and apoptosis was examined by methyl thiazolyl tetrazolium and flow cytometry analysis. The expression of Bax, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 21 publications
1
62
0
Order By: Relevance
“…Bcl-2/Bax heterodimers were increased and eliminated the pro-apoptotic role of Bax along with the Bcl-2 protein expression were increased, so the role of inhibits apoptosis were enhanced. On the other hand, Bax/Bax homodimers were increased when Bax protein expression were increased, the role of pro-apoptotic were enhanced [11,12]. The results of this study show that after A549 cells treated with 2-15 mmol/L oxymatrine for 48 h, Bax protein expression were increased significantly compared with the negative control; on the contrary, the expression of Bcl-2 were reduced significantly.…”
Section: Discussionsupporting
confidence: 44%
“…Bcl-2/Bax heterodimers were increased and eliminated the pro-apoptotic role of Bax along with the Bcl-2 protein expression were increased, so the role of inhibits apoptosis were enhanced. On the other hand, Bax/Bax homodimers were increased when Bax protein expression were increased, the role of pro-apoptotic were enhanced [11,12]. The results of this study show that after A549 cells treated with 2-15 mmol/L oxymatrine for 48 h, Bax protein expression were increased significantly compared with the negative control; on the contrary, the expression of Bcl-2 were reduced significantly.…”
Section: Discussionsupporting
confidence: 44%
“…Oxymatrine can also induce apoptosis in human pancreatic cancer PANC-1 cells by a mechanism similar to matrine. After treatment with oxymatrine, livin and survivin genes were down-regulated and the Bax/Bcl-2 ratio was increased, accompanied by the release of mitochondrial cytochrome c and the activation of caspase-3 protein in PANC-1 cells [24] . It is also suggested that oxymatrine combined with angiogenesis inhibitor NM-3 has a synergistic inhibitory effect on the growth of human gastric cancer SGC-7901, MKN-45, and MKN-74 cells in a time-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported that EEHDW inhibited the growth of HT-29 cells by inducing cell morphological changes, which reduce the cell viability due to DNA fragmentation and loss of plasma membrane asymmetry, and also the collapse of mitochondrial membranes, the activation of caspase-9 and caspase-3 and the increase of the pro-apoptotic Bax to anti-apoptotic Bcl-2 ratio. Oxymatrine (19) is an isolated extract from the traditional Chinese herb Sephora flavescent Ait, and its anticancer effect was examined on human pancreatic cancer PANC-1 cells. The results showed its efficacy by releasing cytochrome c and activating caspase-3 proteins.…”
Section: Inducing Cellular Apoptosismentioning
confidence: 99%